Risk of mortality and cause of death according to kidney function parameters: a nationwide observational study in Korea - Sehyun Jung; Soojin Lee; Yaerim Kim; Semin Cho; Hyuk Huh; Yong Chul Kim; Seung Seok Han; Hajeong Lee; Jung Pyo Lee; Kwon Wook Joo; Chun Soo Lim; Yon Su Kim; et al. (The Korean Society of Nephrology, 2024)
Background Further study is warranted to determine the association between estimated glomerular filtration rate (eGFR) or albuminuria and the risk of death from diverse causes. Methods We screened >10 million general health screening examinees who received health examinations conducted in 2009 using the claims database of Korea. After the exclusion of those previously diagnosed with renal failure and those with missing data, 9,917,838 individuals with available baseline kidney function measurements were included. The primary outcome was mortality and cause-specific death between 2009 and 2019 identified through death certificates based on the diagnostic codes of International Classification of Diseases, 10th revision. Multivariable Cox regression analysis adjusted for various clinicodemographic and social characteristics was used to assess mortality risk. Results The hazard ratio of death was significantly high in both the eGFR <60 mL/min/1.73 m2 and in the eGFR ≥120 mL/min/1.73 m2 groups in univariable and multivariable regression analyses when compared to those within the reference range (eGFR of 90-120 mL/min/1.73 m2). The results were similar for death by cardiovascular, cancer, infection, endocrine, respiratory, and digestive causes. We also found that albuminuria was associated with higher risk of death regardless of eGFR range, and those in the higher categories of dipstick albuminuria showed higher risk. Conclusion We reconfirmed the significant association between eGFR, albuminuria, and mortality. Healthcare providers should keep in mind that albuminuria and decreased eGFR as well as kidney hyperfiltration are independent predictors of mortality.